Economic forecasting - Carnot, Nicolas 1973-; Koen, Vincent 1960-; Tissot, Bruno 1966- (Palgrave Macmillan, 2005)
"[Economic Forecasting] provides a comprehensive overview of macroeconomic forecasting. It focuses first on a large range of theories as well as empirical techniques: business cycle analysis, time series methods, macroeconomic models, medium and long-run projections, fiscal and financial forecasts, and sectoral forecasting. The book then addresses the main issues surrounding the use of forecasts, including accuracy and communication challenges, as well as their policy implications. A tour of the economic data and forecasting institutions is also provided." -- Book cover.
Includes bibliographical references and index
Keywords: Prévision économique; Economic forecasting; Prognoseverfahren; Prognose; Wirtschaftsentwicklung; Wirtschaft